2019
DOI: 10.1002/iub.2178
|View full text |Cite
|
Sign up to set email alerts
|

The roles and controls of GATA factors in blood and cardiac development

Abstract: GATA factors play central roles in the programming of blood and cardiac cells during embryonic development. Using the experimentally accessible Xenopus and zebrafish models, we report observations regarding the roles of GATA-2 in the development of blood stem cells and GATA-4, -5, and -6 in cardiac development.We show that blood stem cells develop from the dorsal lateral plate mesoderm and GATA-2 is required at multiple stages. Firstly, GATA-2 is required to make the cells responsive to VEGF-A signalling by dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In this study, when the teratogenic effects of n‐butanol on the embryos and larvae of Zebrafish were examined, we found that the highest rate of malformation was for cardiac edema. At high doses of n‐butanol (500, 750, and 1,000 mg/L), cardiac edema was observed to circulate in the tail vein and artery veins of larvae at 96 h; thus, we assume that endothelial cells in the vessels are affected by n‐butanol and cause cardiac edema (Jiang et al 2017; Ku et al 2017; Dobrzycki et al 2020). Similarly, high doses of n‐butanol (500, 750, and 1,000 mg/L) are thought to cause abnormalities in heart morphology and decrease heart rate, stopping blood circulation and weakening the heart muscle and causing inadequate blood pressure in the vein (Tanaka et al 2016; Walton et al 2019).…”
Section: Discussionmentioning
confidence: 96%
“…In this study, when the teratogenic effects of n‐butanol on the embryos and larvae of Zebrafish were examined, we found that the highest rate of malformation was for cardiac edema. At high doses of n‐butanol (500, 750, and 1,000 mg/L), cardiac edema was observed to circulate in the tail vein and artery veins of larvae at 96 h; thus, we assume that endothelial cells in the vessels are affected by n‐butanol and cause cardiac edema (Jiang et al 2017; Ku et al 2017; Dobrzycki et al 2020). Similarly, high doses of n‐butanol (500, 750, and 1,000 mg/L) are thought to cause abnormalities in heart morphology and decrease heart rate, stopping blood circulation and weakening the heart muscle and causing inadequate blood pressure in the vein (Tanaka et al 2016; Walton et al 2019).…”
Section: Discussionmentioning
confidence: 96%
“…In zebrafish, however, MO knockdown of gata5 and gata6 resulted in cardia bifida and substantial reduction in expression of contractile protein genes, whereas gata4 morphant cardiomyocytes migrated to the midline normally [ 74 ]. The difference in phenotype severity of gata5 morphants in Xenopus and zebrafish suggests a change in the activity of these GATA factors during evolution [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutants affecting FGF signaling have been among the earliest isolated heart anomalies in zebrafish, as illustrated with the mutant for fgf8 ( ace ) that features predominant ventricle defects [ 54 ]. FGF signaling is deployed at various stages during mesoderm and cardiovascular fate patterning, starting with dorso-ventral patterning during gastrulation, to drive cardiac fate and restrict anterior endothelial-hematopoietic fates in early somitogenesis, and in controlling nkx2.5 and gata4 expression in cardiac precursors [ 54 , 105 , 106 , 107 ]. Perturbations of FGF signaling during the medial migration of the ALPM progenitors reduce ventricle size and inhibit BA formation, possibly suggesting a spatial or temporal sensitivity to FGF signaling in the anterior-posterior patterning of the OFT region [ 89 , 107 ].…”
Section: Developmental Signaling In Early Heart Developmentmentioning
confidence: 99%